Optical properties of condensed matter and applications (John Wiley, 2006)
Following a semi-quantitative approach, this book presents a summary of the basic concepts, with examples and applications, and reviews recent developments in the study of optical properties of condensed matter systems. Key Features: Covers basic knowledge as well as ; opplication topics; Includes theory, experimental techniques and current and developing applications; Timely and useful contribution to the literature; Written by internationally respected contributors working in physics and electrical engineering departments and government laboratories